Assessment of Pain Sensitivity in Patients With Chronic Low Back Pain and Association With HTR2A Gene Polymorphism - Saliha Handan YILDIZ,; Alper Murat ULAŞLI,; Müjgan ÖZDEMİR ERDOĞAN,; Ömer DİKİCİ,; Evrim Suna ARIKAN TERZİ,; Ümit DÜNDAR,; Mustafa SOLAK, (Archives of Rheumatology, 2017)
Objectives: This study aims to investigate the association of two common HTR2A gene polymorphisms, rs6313 (102 T/C) and rs6311 (1438 A/G), with chronic low back pain (CLBP) and the pain threshold, disability, and sex differences. Patients and methods: A total of 121 patients (40 males, 81 females; mean age 36.8±9.9 years; range 18 to 50 years) having CLBP and 91 healthy controls (26 males, 65 females; mean age 34.1±10.2 years; range 18 to 55 years) were included. Pressure pain thresholds (PPTs) of all participants were examined with manual algometer in certain sites of their body. Results: The PPTs were all decreased in CLBP patients (p<0.05). Although PPTs were lower in healthy female subjects, there was no sex difference regarding PPTs in CLBP patients (p>0.05). rs6311 polymorphism of HTR2A gene was associated with CLBP (p<0.05). In rs6313 polymorphism, at least one copy of T carriers and in rs6311 polymorphism, at least one copy of G carriers showed higher disability. Conclusion: The PPT decreases in CLBP patients similar to other chronic pain conditions without any sex difference. Although rs6311 single nucleotide polymorphism of HTR2A gene was associated with CLBP and rs6313 polymorphism was not, rs6311 might have a protective effect on disability of these patients.